The disease resistance protein SNC1 represses the biogenesis of microRNAs and phased siRNAs. Issue 1 (December 2018) - Cai, Qiang; Liang, Chao; Wang, Suikang; Hou, Yingnan; Gao, Lei; Liu, Li; He, Wenrong; Ma, Wenbo; Mo, Beixing; Chen, Xuemei
Abstract Plants evolved an array of disease resistance genes (R genes) to fight pathogens. In the absence of pathogen infection, NBS-LRR genes, which comprise a major subfamily ofR genes, are suppressed by a small RNA cascade involving microRNAs (miRNAs) that trigger the biogenesis of phased siRNAs (phasiRNAs) fromR gene transcripts. However, whether or howR genes influence small RNA biogenesis is unknown. In this study, we isolate a mutant with global defects in the biogenesis of miRNAs and phasiRNAs inArabidopsis thaliana and trace the defects to the over accumulation and nuclear localization of an R protein SNC1. We show that nuclear SNC1 represses the transcription of miRNA and phasiRNA loci, probably through the transcriptional corepressor TPR1. Intriguingly, nuclear SNC1 reduces the accumulation of phasiRNAs from three sourceR genes and concomitantly, the expression of a majority of the 170R genes is up-regulated. Taken together, this study suggests anR gene-miRNA-phasiRNA regulatory module that amplifies plant immune responses. A small RNA-based signaling cascade prevents the induction of plant resistance genes (R -genes) in the absence of pathogen challenge. Here Caiet al . show that nuclear accumulation of the R protein SNC1 can activate immunity by suppressing small RNA production and releasingR -gene repression.